Spiritual Shakespeares - Fernie, Ewan (Accents on Shakespeare, 2005)
Spiritual Shakespeares is the first book to explore the scope for reading Shakespeare spiritually in the light of contemporary theory and current world events. Ewan Fernie has brought together an exciting cast of critics in order to respond to the 'religious turn' in recent literary theory and to the spiritualized politics of terrorism and the 'War on Terror'. Exploring a genuinely new perspective within Shakespeare Studies, the volume suggests that experiencing the spiritual intensities of the plays could lead us back to dramatic intensity as such. It tests spirituality from a political perspective, as well as subjecting politics to an unusual spiritual critique. Amongst its controversial and provocative arguments is the idea that a consideration of spirituality might point the way forward for materialist criticism. Reaching across and beyond literary studies to offer challenging and powerful contributions from leading scholars, this book